2021
DOI: 10.1039/d1sc02213j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of photocatalytic CO2 reduction using a Ru(ii)–Re(i) supramolecular photocatalyst

Abstract: Supramolecular photocatalysts comprising [Ru(diimine)3]2+ photosensitiser and fac-[Re(diimine)(CO)3{OC(O)OC2H4NR2}] catalyst units can be used to reduce CO2 to CO with high selectivity, durability and efficiency. In the presence of triethanolamine, the Re...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 41 publications
5
52
0
Order By: Relevance
“…Based on previous work [17,18,[43][44][45][46] and the above experimental investigations, we propose the mechanism for all these photocatalytic systems shown in Figure 11. At first, the Re complex is photochemically excited to generate the 1 Re* species, and then the species could rapidly undergo ISC, forming 3 Re* states in order to participate in the photocatalytic electron transfer process.…”
Section: Mechanistic Discussionmentioning
confidence: 85%
“…Based on previous work [17,18,[43][44][45][46] and the above experimental investigations, we propose the mechanism for all these photocatalytic systems shown in Figure 11. At first, the Re complex is photochemically excited to generate the 1 Re* species, and then the species could rapidly undergo ISC, forming 3 Re* states in order to participate in the photocatalytic electron transfer process.…”
Section: Mechanistic Discussionmentioning
confidence: 85%
“…Here, DMSO is a suitable solvent for the photocatalytic CO 2 reduction using a Re diimine tricarbonyl complex in the presence of BIH and TEOA. 38 Under micromolar-order concentration conditions, ReDRe dissociated into the corresponding monomer (Figure 9). The first oxidation and reduction potentials of the porphyrin dimer D' and monomer D (Scheme 3) were almost same in DMSO in differential pulse voltammetry (DPV) (Figure S95) and the potentials of ReD'Re were similar to those in DMA.…”
Section: Scheme 3 Synthesis Of the Heterodimer Red'mentioning
confidence: 99%
“…They demonstrated that the triethanolamine ligand on the catalyst moiety reacts with CO 2 to produce a carbonate ester complex, which then subsequently gets reduced to CO. This phenomenon was found beneficial in the sense that even lower concentrations of CO 2 (10%) could get reduced efficiently …”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was found beneficial in the sense that even lower concentrations of CO 2 (10%) could get reduced efficiently. 192 2.7. Selection of the Semiconductor Component.…”
Section: Table 1 Continuedmentioning
confidence: 99%